2022
DOI: 10.1186/s12879-022-07421-3
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in COVID-19 patients and prediction model: a multicenter cohort study

Abstract: Background Patients with COVID-19 infection are commonly reported to have an increased risk of venous thrombosis. The choice of anti-thrombotic agents and doses are currently being studied in randomized controlled trials and retrospective studies. There exists a need for individualized risk stratification of venous thromboembolism (VTE) to assist clinicians in decision-making on anticoagulation. We sought to identify the risk factors of VTE in COVID-19 patients, which could help physicians in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 37 publications
9
29
0
Order By: Relevance
“…Regarding the small sample size, further analyses on larger sample sizes are required to determine the predictors of thrombosis in COVID-19. Interestingly, based on logistic and linear regression models in a multicenter large cohort study on 3531 patients, CRP and LDH were unable to predict thromboembolism in COVID-19, which is in accordance with the present study (20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the small sample size, further analyses on larger sample sizes are required to determine the predictors of thrombosis in COVID-19. Interestingly, based on logistic and linear regression models in a multicenter large cohort study on 3531 patients, CRP and LDH were unable to predict thromboembolism in COVID-19, which is in accordance with the present study (20).…”
Section: Discussionsupporting
confidence: 92%
“…The variables, including mean age, mean day of hospitalization, PaO 2 saturation, levels of CRP and ESR, and lymphocyte count, showed no significant differences between the thrombotic and non-thrombotic groups. Parallel to this finding, Lee et al also reported no significant difference in oxygen saturation between thrombotic and nonthrombotic COVID-19 patients (20). Riyahi et al conducted a multicenter study on 413 COVID-19 patients and found pulmonary embolism in 25% of hospitalized patients (11).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is a retrospective, multi-institutional (one quaternary care and three community hospitals) cohort study of patients older than 18 years old admitted with polymerase chain reaction proven SARS-CoV-2 infection between March 1, 2020, and September 5, 2021. Data were analyzed from the Southeast Michigan COVID-19 Consortium Registry Database, a multi-institutional database of four main health systems in southeast Michigan, United States, including Henry Ford Health System, Beaumont Health System, Trinity Health System, and Wayne State University 15 , 16 . Data from Trinity and Henry Ford Health were used for this particular study.…”
Section: Methodsmentioning
confidence: 99%
“…30 Similarly, Lee et al also evidenced that a multivariable model including both clinical and laboratory parameters (i.e., blood pressure, creatinine, electrolytes, hepatic enzymes and inflammatory biomarkers) predicted in-hospital VTE in COVID-19 patients with 0.83 AUC, 0.68 sensitivity, and 0.82 specificity, respectively. 31 Even the use of protocols including anticoagulant escalation based on D-dimer values enables to reduce the risk of death compared with standard thromboprophylaxis, 32 thus reinforcing the concept that a “personalized” treatment may be perhaps better than recommending a “standard” anticoagulant strategy.…”
Section: Tablementioning
confidence: 99%